2013
DOI: 10.1038/nn.3596
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hematopoietic TNF, via milk chemokines, programs hippocampal development and memory

Abstract: TNF is a proinflammatory cytokine with established roles in host defense and immune system organogenesis. Here we report a novel physiological function of TNF that extends its effect beyond the host into the developing offspring. A partial/complete maternal TNF-deficit, specifically in hematopoietic cells, resulted in reduced milk levels of chemokines IP-10, MCP-1/−3/−5, and MIP-1β, which in turn, augmented offspring postnatal hippocampal proliferation, leading to improved adult spatial memory in mice. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 60 publications
3
44
0
1
Order By: Relevance
“…Taken together, the results presented in this study establish that, as reported for the neonatal porcine uterus and testis (Rahman et al 2014), as well as for the murine hippocampus (Liu et al 2014), lactocrine support is necessary for normal development of the neonatal porcine cervix. Disruption of cervical development by transient imposition of the lactocrine-null state for 2 days from birth altered the cervical developmental program in a manner that, as assessed on PND14, could not be reversed by returning gilts to nursing in synchrony with their littermates.…”
Section: Discussionsupporting
confidence: 88%
“…Taken together, the results presented in this study establish that, as reported for the neonatal porcine uterus and testis (Rahman et al 2014), as well as for the murine hippocampus (Liu et al 2014), lactocrine support is necessary for normal development of the neonatal porcine cervix. Disruption of cervical development by transient imposition of the lactocrine-null state for 2 days from birth altered the cervical developmental program in a manner that, as assessed on PND14, could not be reversed by returning gilts to nursing in synchrony with their littermates.…”
Section: Discussionsupporting
confidence: 88%
“…rat: Prado et al, 1997; red deer: Landete-Castillejos et al, 2001; rhesus macaque: Hinde et al, 2009; reviewed in Hinde, 2013), and neurobehavioral development (rat: Catalani et al, 2011; Liu et al, 2014; rhesus macaque: Dettmer et al, 2017; reviewed in Dettmer, et al 2014). To date, how the age of reproductive debut influences lactational performance remains largely unexplored.…”
mentioning
confidence: 99%
“…Female pups receiving poor maternal care will also show reduced maternal behaviors themselves, which is associated with epigenetic dysregulation in the brain (Weaver et al 2004 ;Champagne 2008 ). Additionally, milk composition during lactation (Liu et al 2014 ), microbiota (Stilling et al 2014 ), or odor cues (Debiec and Sullivan 2014 ) can also transfer environmental experiences from mother to offspring.…”
Section: Appendix 1: Experimental Methods To Examine Different Routesmentioning
confidence: 99%